Effects of Effortful Swallow on Cardiac Autonomic Regulation - Gomes, Lívia M. S. [UNESP]; Silva, Roberta G. [UNESP]; Melo, Monique [UNESP]; Silva, Nayra N. [UNESP]; Vanderlei, Franciele M. [UNESP]; Garner, David M.; de Abreu, Luiz Carlos; Valenti, Vitor E. [UNESP] (Springer Nature, 2016)
Swallowing-induced changes in heart rate have been recently reported. However, it is not apparent the responses of heart rate variability (HRV) elicited by effortful swallow maneuver. We investigated the acute effects of effortful swallowing maneuver on HRV. This study was performed on 34 healthy women between 18 and 35 years old. We assessed heart rate variability in the time (SDNN, RMSSD, and pNN50) and frequency (HF, LF, and LF/HF ratio) domains and, visual analysis through the Poincaré plot. The subjects remained at rest for 5 min during spontaneous swallowing and then performed effortful swallowing for 5 min. HRV was analyzed during spontaneous and effortful swallowing. We found no significant differences for SDNN, pNN50, RMSSD, HF in absolute units (ms2). There is a trend for increase of LF in absolute (p = 0.05) and normalized (p = 0.08) units during effortful swallowing. HF in normalized units reduced (p = 0.02) during effortful swallowing and LF/HF ratio (p = 0.03) increased during effortful swallowing. In conclusion effortful swallow maneuver in healthy women increased sympathetic cardiac modulation, indicating a cardiac overload.
Keywords: Autonomic nervous system; Cardiovascular system; Deglutition; Deglutition disorders; Heart rate variability